Superconductivity and fluctuations in Ba1–pKpFe2As2 and Ba(Fe1–nCon)2As2. Issue 1 (11th August 2016) - Böhm, T.; Hosseinian Ahangharnejhad, R.; Jost, D.; Baum, A.; Muschler, B.; Kretzschmar, F.; Adelmann, P.; Wolf, T.; Wen, H.‐H.; Chu, J.‐H.; Fisher, I. R.; Hackl, R.
Abstract: We study the interplay of fluctuations and superconductivity in BaFe2 As2 (Ba‐122) compounds with Ba and Fe substituted by K (p doping) and Co (n doping), respectively. To this end, we measured electronic Raman spectra as a function of polarization and temperature. We observe gap excitations and fluctuations for all doping levels studied. The response from fluctuations is much stronger for Co substitution and, according to the selection rules and the temperature dependence, originates from the exchange of two critical spin fluctuations with characteristic wave vectors ( ± π, 0 ) and ( 0, ± π ) . At 22% K doping ( p = 0.22 ), we find the same selection rules and spectral shape for the fluctuations but the intensity is smaller by a factor of 5. Since there exists no nematic region above the orthorhombic spin‐density‐wave (SDW) phase, the identification of the fluctuations via the temperature dependence is not possible. The gap excitations in the superconducting state indicate strongly anisotropic near‐nodal gaps for Co substitution which make the observation of collective modes difficult. The variation with doping of the spectral weights of the A 1 g and B 1 g gap features does not support the influence of fluctuations on Cooper pairing. Therefore, the observation of Bardasis–Schrieffer modes inside the nearly clean gaps on the K‐doped side remains the only experimental evidence for the relevance of fluctuations for pairing.